Association between fluid balance and mortality in patients with septic shock: a post hoc analysis of the TRISS trial. Issue 7 (31st March 2016) - Cronhjort, M.; Hjortrup, P. B.; Holst, L. B.; Joelsson‐Alm, E.; Mårtensson, J.; Svensen, C.; Perner, A.
Abstract : Background: Several studies have shown an association between a positive fluid balance and increased mortality in patients with septic shock. This may have led to a more restrictive use of intravenous fluids. The association between fluid accumulation and mortality in the setting of a more restrictive use of intravenous fluids, however, is uncertain. We therefore aimed to investigate the association between a cumulative fluid balance 3 days after randomization and 90‐day mortality in a recent Nordic multicentre cohort of patients with septic shock. Methods: A post hoc analysis of patients from the Transfusion Requirements in Septic Shock (TRISS) trial treated for 3 days or more in the ICU after randomization. The patients were categorized into four groups depending on their weight‐adjusted cumulative fluid balance after 3 days. We performed multivariable Cox regression analysis, adjusting for important prognostics (study site, age, chronic cardiovascular and chronic lung disease, haematologic malignancy, chronic dialysis, source of infection, baseline SOFA score and plasma lactate). Results: The median cumulative fluid balance of the 841 included patients was 2480 ml (IQR 47‐5045). The median time from ICU admission to inclusion in the trial was 22 h. The overall 90‐day mortality was 52%. There was no statistically significant association between fluid balance 3 days from inclusion and 90‐day mortality after the adjustment for the prognostics ( P = 0.37). Conclusion: In our cohort of patients with septic shock and a comparably low cumulative fluid balance, there was no association between fluid balance and mortality. However, the study design and the limited power preclude strong conclusions. There is an urgent need for high‐quality trials assessing the benefit and harm of different fluid volume strategies in patients with septic shock.